2020
DOI: 10.1002/adom.202001572
|View full text |Cite
|
Sign up to set email alerts
|

Swallow‐Tailed Polycatenars: Controlling Complex Liquid Crystal Self‐Assembly and Mirror Symmetry Breaking at the Lamellae‐Network Cross‐Over

Abstract: molecules in soft self-organized supramolecular systems. [1,2] Extended π-conjugated systems are also of significant interest for application as charge carrier in organic semiconductors, [3] luminescent materials (e.g., AIEgens), [4] and for circular polarized emission in helical assemblies. [5] Therefore, tuning the organization of these π-conjugated rods in soft matter systems is fundamental and requires the understanding of their general design rules. Liquid crystals (LCs) are of great interest as stimuli-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 145 publications
(200 reference statements)
0
11
0
Order By: Relevance
“…[ 39 , 40 ] However, recently it was found that there is another type of Cub bi phase which is chiral and forms conglomerates of chiral domains with opposite handedness. [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] This is due to the triple network structure of this Cub bi phase with space group I 23 (Figure 1 b), [52] previously known as Im m . [ 53 , 54 , 55 , 56 , 57 ] In this case the network chirality cannot cancel out and a conglomerate of chiral domains is observed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 , 40 ] However, recently it was found that there is another type of Cub bi phase which is chiral and forms conglomerates of chiral domains with opposite handedness. [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] This is due to the triple network structure of this Cub bi phase with space group I 23 (Figure 1 b), [52] previously known as Im m . [ 53 , 54 , 55 , 56 , 57 ] In this case the network chirality cannot cancel out and a conglomerate of chiral domains is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated lattice parameter a cub is 11.30 nm, which is in the expected range of this type of cubic phase. 11,14,15,27,28 The additional small reflection peaks could be also indexed to Cub bi /Ia% 3d phase (see Table S1 in the ESI †). The reconstructed electron density map based on the obtained diffraction patterns, shows the double gyroid network structure of the Ia % 3d phase (Fig.…”
Section: Hockey-stick Polycatenars B6/nmentioning
confidence: 99%
“…Cub [ * ] with I23 symmetry (Cub [ * ] /I23) as would be expected upon alkyl-chain elongation. 14,15,28 However, the type of the Cub bi does not change with increasing the length of the terminal chains, indicating that the required chain volume is not achieved.…”
Section: Hockey-stick Polycatenars B10/nmentioning
confidence: 99%
See 2 more Smart Citations